Trying to understand the reasons of residential mobility through a quantitative approach: case study in Constantine - Djeghar, Aïda (Journal of Human Sciences, 2020)
Through this study, we are interested in understanding and interpreting the junctions between the reasons of residential mobility and socio-professional classes among households in two housing parks (collective and chalets) in Constantine, using an approach both quantitative and socio-spatial in data processing and analysis.